Understanding Mechanisms Driving Family Homeless Shelter Use and Child Mental Health. Issue 47 (4th July 2021) - Marçal, Katherine E.; Fowler, Patrick J.; Hovmand, Peter S.; Cohen, Jessica
Abstract: Homeless shelters throughout the U.S. are overcrowded and under-resourced. Families with children face substantial barriers to timely, successful shelter exit, and prolonged shelter stays threaten child mental health. This community-based system dynamics study explored barriers to timely, successful shelter exit and feedback mechanisms driving length of stay and child mental health risk. Group model building – a participatory systems science tool – and key informant interviews were conducted with clients (N = 37) and staff (N = 6) in three family homeless shelters in a Midwestern region. Qualitative content analysis with emergent coding identified key themes feedback loops. Findings indicated overcrowding delayed successful shelter exit; longer stays exacerbated crowding and stress in a vicious cycle. Furthermore, longer stays exacerbated child risk for mental disorder both directly and indirectly via crowding and caregiver stress. Capacity constraints limited families served, while contributing to ongoing unmet need. Future research should investigate the roles of these dynamic feedback relationships in the persistent vulnerability of homeless families. Service design should prioritize interventions that alleviate crowding and subsequent threats to mental health such as private or scattered-site shelter accommodations, affordable child care, and homelessness prevention to facilitate successful shelter exit and mitigate child mental health risk.